Pricing the strategic value of putable securities in liquidity crises - David, Alexander (Journal of Financial Economics, 2001)
Putable security holders have a de facto first claim on the firm's liquid assets and can threaten to force solvent issuers to bear financial distress costs. Their threatening power implies that the puts have a strategic value larger than their intrinsic value. Strategic value depends on the issuer's size, potential distress costs, and the distribution of put ownership relative to the firm's liquidity position. The analysis of Kmart's put-induced crisis in 1995, and a calibration to observed secondary market yield reductions on poison put bonds, shows that strategic value is an important determinant of payouts received by bondholders.